Sistem Informasi Pemberian Bonus Karyawan Operasional Menggunakan Metode Simple Additive Weghting (SAW) - Devi Utari; Permata; Agus Wantoro (Jurnal Media Borneo, 2023)
PT Pinus Merah Abadi Branch of Liwa West Lampung has bonuses given to employees in the operational section but so the evaluation of employee bonuses has only been based on the subjective assessment of superiors not based on other components, resulting in the evaluation of employee bonuses being constrained. Lack of transparency in assessment. The system development method uses the Extreme Programming method and system design uses UML. The implementation of this system uses PHP and MySQL as databases, and system testing uses ISO25010. The result achieved is a decision support system for determining employee bonuses using the Simple Additive Weighting method. The results of ISO 25010 testing which was carried out involving 27 respondents concluded that the quality of the feasibility of the resulting software has a percentage of success with a total average of 90.88%.